2019
DOI: 10.3390/met9010090
|View full text |Cite
|
Sign up to set email alerts
|

Dislocations Help Initiate the α–γ Phase Transformation in Iron—An Atomistic Study

Abstract: Using molecular dynamics simulation, we studied the influence of pre-existing dislocations on the austenitic and the martensitic phase transformations in pure iron. The simulations were performed in a thin-film geometry with (100) surfaces. We found that dislocations alleviate the transformation by lowering the austenitic transformation temperature and increasing the martensitic transformation temperature. In all cases, the new phase nucleates at the dislocations. The orientation relationships governing the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The transition barrier is 7 meV/atom at this temperature [ 33 ]. In studies using the Meyer-Entel potential, inclusive of this work, the austenitic temperatures were always above the equilibrium temperature, and the martensitic temperatures were always below it [ 14 , 17 , 30 ]. In the phase transition induced by temperature changing, the finite heating/cooling rate should be the reason for this hysteresis as a result of the kinetic effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition barrier is 7 meV/atom at this temperature [ 33 ]. In studies using the Meyer-Entel potential, inclusive of this work, the austenitic temperatures were always above the equilibrium temperature, and the martensitic temperatures were always below it [ 14 , 17 , 30 ]. In the phase transition induced by temperature changing, the finite heating/cooling rate should be the reason for this hysteresis as a result of the kinetic effect.…”
Section: Resultsmentioning
confidence: 99%
“…In the bulk material, crystal defects influent the transition behavior of Fe dramatically. Grain boundaries (GBs) [ 13 ], twin boundaries (TBs) [ 14 ] or dislocations [ 15 , 16 , 17 ] often act as the nucleation sites of the new phase. However, the influence of crystal defects on the transition in nanoscaled systems is still under discussion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies are related to this issue. In the nanoscale system, Meiser and Urbassek [29] simulated the Fe thin films containing dislocations and reported the thermally induced phase transition is initiated at the dislocation positions in despite of the existence of free surface. Here we should note that dislocation is only one defect type in the material.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this choice is that TBs normally exhibit smaller energy compared to dislocations or grain boundary (GB). Since it has been confirmed that dislocations assist the phase transition in Fe thin films [29], it is meaningful to check whether another type of defect (TB), which is energetically more stable, has similar effect. In the present work, biaxial tensile strains will be applied to the bcc Fe thin films containing various TBs.…”
Section: Introductionmentioning
confidence: 99%